Keith Price annotated computer vision bibliography: 16.7.4.4.3 Human Motion Capture, Joint Information, Dance, Special Activities - Price, K. (2010)
This is a annotated bibliography of computer vision papers accumulated over a number of years. Papers are grouped into chapters and sections by general topic using some obscure classification scheme. Annotations have been added at various times, but are not complete. Within each section, papers are generally arranged with the oldest journal papers first then the conference papers, but conference papers related to specific journal papers are often grouped with the journal paper.